Raft-Synthesized Poegma-B Block Copolymers: Preparation of Nanosized Micelles for Anticancer Drug Release - Bayram, Nazende Nur; Topuzogullari, Murat; Isoglu, Ismail Alper; Isoglu, Sevil Dincer; Dinçer İşoğlu, Sevil (Springer, 2021)
To achieve high stability and biocompatibility in physiological environment, oligoethyleneglycol methacrylate (OEGMA) and 4-vinylpyridine (4VP)-based amphiphilic block copolymers were prepared as micellar carriers to deliver doxorubicin into tumor cells. First, macroinitiator of OEGMA was synthesized by RAFT polymerization at [M](0)/[CTA](0)/[I](0) ratio of 100/1/0.2 in dimethylformamide (DMF) at 70 degrees C, in the presence of 4,4'-azobis(4-cyanovaleric acid) (ACVA) as initiator and 4-cyano-4-(thiobenzoylthio)pentanoic acid (CTA) as chain transfer agent, respectively. It was followed by copolymerization with 4-VP at similar conditions. The formation of RAFT-mediated polymers was approved by FTIR, H-1-NMR and GPC. For the preparation of drug-loaded micelles, a dialysis method was applied and hydrophobic doxorubicin, as a model drug, was entrapped into the micelles. Size distributions and morphologies of drug-loaded micelles were investigated by light scattering and scanning electron microscopy, respectively. Critical micelle concentration was estimated as 0.0019 mg/mL by measuring light scattering intensity in different polymer concentrations. Also, drug loading and entrapment efficiencies were calculated as 4.41% and 17.65% by measuring the DOX amount in the micelles, spectrophotometrically. At last, the drug-loaded micelles were applied to SKBR-3 breast cancer cell lines and revealed up to %40 cell inhibition at 48 and 72 h. As a result, these nanosized and biocompatible micelles can be used for the delivery of hydrophobic drugs, and they can also be modified for further targeting and imaging applications toward specific cancer cells. [GRAPHICS] .
Bayram, Nazende Nur/0000-0002-8697-1654; Topuzogullari, Murat/0000-0003-4435-7776;
Keywords: Ph-Responsive; Micelle Nanocarrier; Raft; Breast Cancer